Preliminary Biochemical Screening and Antibacterial Activities of Hygrocybe Cantharellus (Schwein.) Murrill - Chittaragi, Ashok; Naika, Raja (Asian Journal of Pharmaceutical Research and Development, 2014)
The present study was carried out to preliminary biochemical screening and antibacterial activities of Hygrocybecantharellus (Schwein.) Murrill on selected three plant and six human bacterial pathogens such as Xanthomonascampestris, Pseudomonas syringae, Agrobacterium tumefaciens, Klebsiella pneumonia, Staphylococcus aureus, Salmonella parathyphi, Salmonella typhi, Pseudomonas aeruoginosa and Escherichia coli. For antibacterial test, well diffusion technique was used and the zone of inhibition of microorganisms was measured in mm. The biochemical analysis of the mushroom extracts of various solvents contained alkaloids, saponins, glycosides, flavonoids and phenols but did not contain detectable levels of steroids, tannins, triterpenoids. The fruit body of H. cantharellus showed potential antibacterial activities against the selected strains and maximum inhibition zone 17 mm followed by 16 mm, 15 mm and 14 mm was recorded from 100 mg of methanol and petroleum ether extracts of H. cantharellus fruit body against P. aereuoginosa followed by S. typhi, A. tumefaciens, S.aureus and X. campestrisand minimum (8 mm and 6 mm) by the S. parathyphi and K. pneumonia at 12.5 mg of extracts.However, the activity was less than the standard tetracycline and ciprofloxacin. The extract shows increasing inhibitory activity with increase in concentration (12.5 % - 100 %).The study concluded that the different solvent extracts of fruiting body of H. cantharellus contain potential compounds that inhibit growth of both plant and human pathogenic bacteria.